A LITERARY REVIEW ON MERCURY W.S.R. TO ITS MEDICINAL ASPECT (AYUSHDHARA, 2016)
Rasasastra is a branch of Ayurvedic medicine dealing with metals and minerals having higher therapeutic efficacy. Recent world wide discussions on hazardous nature of Mercury have led to the global ban on Mercury through Minamata Convention. This is a crisis situation for Ayurveda as Parada (Mercury) is the heart of Rasasastra. An attempt has been made to educate the readers regarding the medicinal aspects of Mercury. Rasasastra texts starting from Rasendra mangalam to Rasatrangini have been analyzed for relevant verses regarding Mercurial formulations with respect to its disease curing property. Mercury has qualities similar to ambrosia. Mercurial medications prepared from purified Mercury can readily treat even Asadhya rogas (incurable diseases). Purified Mercury samples were tested for their therapeutic efficacy through alchemy. A systematic classification regarding types of Mercury, their impurities and purification procedures are mentioned after extensive research in Rasasastra. Method of intake, Pathya (wholesome), Apathya (unwholesome), complications during Mercurial medication have been cited in classical verses. Paribhasha (definitions) regarding basics of Rasasastra have been described for better understanding of Mercurial processes. Procedures like Jarana (digestion), Astadasa samskara (eighteen purification procedures), Dhruti (stable liquid metal), Satwapatana (extracting the essence), Bandhana, etc have been elaborately described in the texts, but their techniques are still unclear in practical aspect. A special clause should be created for the use of Mercury in Ayurvedic medicines with respect to its health benefits and disease curing properties. Also there is a need to intensify research in the field of Rasasastra.